Genetic Alterations in Papillary Thyroid Carcinoma With Hashimoto’s Thyroiditis： ANK3, an Indolent Maintainer of Papillary Thyroid Carcinoma - Zeng, Chao; Long, Jiali; Deng, Chunmiao; Xie, Linying; Ma, Hongmei; Guo, Yimin; Liu, Shuguang; Deng, Min (Frontiers in Oncology, 2022)
Hashimoto's thyroiditis (TH) is a risk factor for the occurrence of papillary thyroid carcinoma (PTC), which is considered to be the most common type of thyroid cancer. In recent years, the prevalence of PTC with TH has been increasing, but little is known about the genetic alteration in PTC with TH. This study analyzed the mutation spectrum and mutation signature of somatic single nucleotide variants (SNV) for 10 non-tumor and tumor pair tissues of PTC with TH using whole-exome sequencing. Moreover, the functional role of ANK3 in PTC cells was determined by CCK-8 proliferation assay, colony formation assays, cell cycle analysis, cell invasion and migration and in vivo study through overexpression assay. Our results showed three distinct mutational signatures and the C>T/G>A substitution was the most common type of SNV. Gene-set enrichment analysis showed that most of the significantly mutated genes were enriched in the regulation of actin cytoskeleton signaling. Moreover, NCOR2, BPTF, ANK3, and PCSK5 were identified as the significantly mutated genes in PTC with TH, most of which have not been previously characterized. Unexpectedly, it was found that ANK3 was overexpressed in the cytomembrane of PTC cells with TH and in almost all PTC cases, suggesting its role as a diagnostic marker of PTC. In addition, our findings revealed that enhanced ANK3 expression inhibits growth of papillary thyroid carcinoma cells both in vitro and in vivo. Ectopic expression of ANK3 significantly enhanced E-cadherin protein expression and inhibited PTC progression, at least in part, by suppression of epithelial-mesenchymal transition (EMT). Our study shows that ANK3 exerts an anti-oncogenic role in the development of PTC and might be an indolent maintainer of PTC.